The language of twentieth-century art : a conceptual history - Crowther, Paul. (New Haven : Yale University Press, 1997)
1 Iterability, Pictorial Representation and Beyond##2 The Structure of Cubism##3 Front Duration to Modernity: Bergson and Italian Futurism##4 Malevich, Philosophy and Non-Objectivity##5 Dialectic and Surrealism: From Breton to Pollock##6 The Dialectic of Abstract-Real in Mondrian##7 Barnett Newman and the Sublime##8 Aesthetic Ideas versus Conceptual Art##9 Simulation and Postmodern Representation##10 The Postmodern Iterable: Installation and Assemblage Art##11Leaving the Twentieth Century: A Future for Art
Includes bibliographical references (p. [235]-246) and index.
boek